THE EFFECT OF COMPETENCY ON LECTURERS' PERFORMANCE WITH ORGANIZATIONAL CULTURE AS AN INTERVENING VARIABLE - Sabar Dumayanti Sihombing; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis (Journal of Information Systems Management and Digital Business, 2026)
The decline in lecturer quality is undoubtedly caused by various internal and external factors. This study will examine the effect of competency on lecturer performance, with organizational culture as an intervening variable at universities in Pematangsiantar. The research method used a quantitative approach. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the aid of SmartPLS software. The sample size was 220. The results of the study show that Organizational Culture (Z) affects Lecturer Performance (Y), with Original Sample (O) = 0.420, T Statistic = 4.416 > 1.96, and P Value = 0.000 < 0.05. This means that organizational culture affects lecturer performance at universities in Pematangsiantar. Similarly, Competence (X) affects Organizational Culture (Z), with Original Sample (O) = 0.334, T Statistic = 3.706 > 1.96, and P Value = 0.000 < 0.05. This means that competence affects Organizational Culture. Furthermore, Competence (X1) affects Lecturer Performance (Y), with Original Sample (O) = 0.244, T Statistic = 3.610 > 1.96, and P Value = 0.000 < 0.05. This means that competence affects Lecturer performance at universities in North Sumatra. Therefore, it can be concluded that organizational competence and culture are necessary for optimal lecturer performance.